Answer:
The mapping statements (-3,7) -> (-9,10) and (1, -5)-> (-5, -2) describe the same translation.
Step-by-step explanation:
In a translation, we have that:
(x,y) -> (x+a,y+b)
In which a and b are how much the values change.
(6.-9) -> (0,1)
x subtracted by 6, y added by 10. So, the translation rule is:
(x,y) -> (x - 6, y + 10).
(-3,7) -> (-9,10)
x subtracted by 6, y added by 3. So
(x,y) -> (x - 6, y + 3).
(1, -5)-> (-5, -2)
x subtracted by 6, y added by 3. So
(x,y) -> (x - 6, y + 3)
Same rule as the above, so the mapping statements (-3,7) -> (-9,10) and (1, -5)-> (-5, -2) describe the same translation.
(2, 4) -> (-4,1)
x subtracted by 6, y subtracted by 3. So
(x,y) -> (x - 6, y - 3)